Myocardial infarction after percutaneous coronary intervention: a meta-analysis of troponin elevation applying the new universal definition. - Testa, L; Van Gaal, W; Biondi Zoccai, G; Agostoni, P; Latini, R; Bedogni, F; Porto, I; Banning, A (2009)
AIM: Elevation of Troponin after scheduled percutaneous coronary intervention (PCI) is a recognized consequence. We sought to evaluate the prognostic significance and impact of the newly published definition of PCI-related myocardial infarction (MI) according to which any troponin elevation >3 times the upper reference limit identify a peri-procedural MI. METHODS: Search of BioMedCentral, CENTRAL, mRCT and PubMed (updated May 2008). Outcomes of interest were: MACE [the composite of all cause death, MI, repeat target vessel PCI (re-PCI) and coronary artery bypass grafting (CABG)]; single end points were also assessed. RESULTS: Fifteen studies have been included totalling 7578 patients. Troponin elevation occurred in 28.7% of the procedures. The incidence of PCI-related MI according to the new definition was 14.5%. During the hospitalization, any level of raised troponin was associated with an increased risk of MACE [OR 11.29 (3.00-42.48), Number needed to harm (NNH) 5], death [OR 7.16 (1.95-26.27), NNH = 100], MI [OR 30.85 (6.05-157.38), NNH = 4] and re-PCI [OR 4.13 (1.23-13.88), NNH = 50]. Patients with PCI-related MI had an increased risk of death [OR 17.25 (2.71-109.96), NNH = 100] and re-PCI [OR 10.86 (3.2-36.94), NNH = 25]. At follow up of 18 months any troponin elevation was associated with an increased risk of MACE [OR 1.48 (1.12-1.96), NNH = 20], death [OR 2.19 (1.59-3.00), NNH = 50], MI [OR 3.29 (2.71-6.31), NNH = 33] and re-PCI [OR 1.47 (1.06-2.03), NNH = 25]. In patients with PCI-related MI the risk of MACE was further increased: OR 2.25 (1.26-4.00), NNH = 3. An increase of the troponin level below the cut-off was not associated with MACE. CONCLUSION: A diagnosis of MI according to the new guidelines applies to 15% of patients undergoing PCI and these patients are at high risk of further adverse events both during the hospital stay and at 18 months.